PENERAPAN DAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI SEBAGAI SARANA DALAM PROSES PEMBELAJARAN DI DUNIA PENDIDIKAN - Sandra Jamu Kuryanti (Cakrawala - Jurnal Humaniora, 2011)
The use of information and communication technology in learning can encourage the emergenceof communication, creativity and able to solve problems faced by the students in learning, becausethis learning process using computer facilities in the learning process. The computer will makestudents more creative. The presence of information and communication technology in educationcan not stand alone, because the information and communication technology consists of thecomponents relate to each other, such as computers, software, information, programming, humanand communication. The purpose of the application and utilization of information andcommunication technology in education are to improve the quality of teaching and learning,improving skills and competency of students and as a source of teaching materials. SMAN 1 LubukLinggau and SMAN 1 Martapura is one of the schools that have implemented and use ofinformation and communication technology as a means of learning processKeywords: I nformation and Communications Technology, Learning Process